Videos in short video sharing platforms as a source of information on bipolar disorder: a cross-sectional content analysis study - Qi, Xin; Lu, Qi; Li, Bo; Liu, Sha; Zhang, Lei; Xiang, Runwu; Wang, Qilong; Zhao, Dongrong (Frontiers in Public Health, 2025)
BackgroundBipolar disorder is a prevalent mental health issue characterized by recurrent episodes of mania and depression, significantly impacting patients’ quality of life. With the rise of short video sharing platforms, there is an urgent need to evaluate the quality and reliability of the medical information disseminated regarding this disorder.ObjectiveThis study aimed to assess the quality and reliability of videos related to bipolar disorder available on popular Chinese short video platforms, including TikTok, Kwai, Bilibili, WeChat, Xiaohongshu, and Baidu.MethodsA cross-sectional content analysis was conducted in May 2025, using keywords related to bipolar disorder to retrieve relevant videos from selected platforms. The quality of the videos was evaluated using multiple standardized assessment tools, including the JAMA Benchmarking Criteria, GQS, modified DISCERN, PEMAT, and HONCODE.ResultsSignificant differences in video quality and audience engagement metrics were observed across platforms. TikTok and Kwai had higher quality scores, while WeChat resulted in more comments. Most videos were created by medical professionals, although independent users also contributed content. Overall, video quality was inconsistent and not necessarily correlated with engagement metrics, highlighting the necessity for improved standards in disseminating health-related information on social media.ConclusionOn Chinese short video platforms, clinical practitioners are the main creators of bipolar disorder-related content, but their scientific nature, production quality, and information transparency still need to be improved. It is suggested to improve the platform management, creator training, and algorithm optimization, so as to promote the improvement of public mental health literacy.